MOBILITAS PENDUDUK ANTAR KITA DI PROPINSI RIAU STUDI KASUS TRANSPORTASI DARAT - Syafnidar, Syafnidar (jurnal ekonomi, 2007)
Population mobility is mean spatial moving or geografis, consist of permanent moving dimention (migration) or non permanent dimention (sirculation and comutation). Population moving from origin region to destination region caused pull factor from destination region like as job vacancy, education facility, rate of salary and push factor from origin region like as income and education also distanse between both region to interaction. Population moving between origin region and destination region will use distanse effect for population mobility. The goal of research to appreciate population mobility between city in Riau and to determine need transportation between city as facility for population mobility fluently. For to get all that using gravity model. The result research is negative correlation between distance with population mobility, its mean if added distance will decrease people want to journey between region.